ISLAM, THE WEST AND LINGUISTIC POLITENESS: A COMPARISON OF POST-SOVIET UZBEKISTAN AND THE UNITED STATES (Konferensiyalar | Conferences, 2024)
Linguistics as a field of knowledge emerged out of an endeavor aimed at giving voice to the colonial subaltern. As a discipline for expressing the diversity of others, it ironically created constructs of language out of processes of the invisibility of voice, the denial of cultural entanglements, and the suppression of experiences, histories, and indigenous languages – processes that were traumatic. Not surprisingly, the imposition of colonial values and meanings on indigenous languages and the “revoicing” of indigenous knowledge created in the colonial subject a feeling of existing absolutely for the other, a psychic split characteristic of feelings of detachment from a sense of integrity, self-worth, and human value.